Pengendalian Progres Biaya dan Waktu dengan Metode Earned Value Analysis Proyek Gedung - Silitonga, Virginia; Khalifah, Via Azizul Saputri; Fansuri, Muhammad Hamzah (Teknik Sipil, Politeknik Negeri Ketapangg, 2025)
Proper planning for a construction project is a vital thing that supports the success of the project. Success in a construction project can be seen from the timeliness and costs that have been determined and planned. During the construction implementation process, delays often occur resulting in temporary stops in a construction project. Therefore, control is needed to overcome deviations that occur, one of which is through the Earned Value Analysis method. The aim of this research is to control the project and identify performance, cost and time indicators in more detail through in-depth analysis. Research on this multi-storey building project occurred under budget in the 1st week to the 37th week because CPI > 1 and over budget occurred in the 38th to 44th week because the CPI < 1. Meanwhile, in the 18th week to the 37th week there was a project delay because the SPI < 1. Based on estimates, there will be an additional cost of 12.80% and an additional time of 4 days. Therefore, there is a need for a solution to overcome time delays or reduce cost overruns.